2021
DOI: 10.5653/cerm.2020.03972
|View full text |Cite
|
Sign up to set email alerts
|

High mRNA expression of GABA receptors in human sperm with oligoasthenoteratozoospermia and teratozoospermia and its association with sperm parameters and intracytoplasmic sperm injection outcomes

Abstract: Objective: This study investigated the mRNA expression of gamma-aminobutyric acid (GABA) receptors in the sperm of oligoasthenoteratozoospermic (OAT) and teratozoospermic (TER) men compared to normozoospermic (NOR) men, as well as the relationships between GABA receptor expression and sperm parameters, fertilization rate, and embryo quality.Methods: The mRNA expression of GABA A-α1 and GABA B-R2 receptors in sperm was examined using reverse transcription–polymerase chain reaction in three groups of patients: N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…In this study, we detected the content of pyruvate in sperm and found a significant increase in pyruvate content in the L group, indicating that pyruvate may regulate sperm motility and function through multiple metabolic pathways. Previous studies suggested that GABA can affect the sperm acrosomal reaction. IL4I1 can produce reactive oxygen species (ROS) and play an important role in regulating sperm function . Our results showed that the protein expression level of IL4I1 in the L group was higher than that in the H group, indicating that it may cause damage to sperm by producing excessive ROS …”
Section: Discussionmentioning
confidence: 59%
“…In this study, we detected the content of pyruvate in sperm and found a significant increase in pyruvate content in the L group, indicating that pyruvate may regulate sperm motility and function through multiple metabolic pathways. Previous studies suggested that GABA can affect the sperm acrosomal reaction. IL4I1 can produce reactive oxygen species (ROS) and play an important role in regulating sperm function . Our results showed that the protein expression level of IL4I1 in the L group was higher than that in the H group, indicating that it may cause damage to sperm by producing excessive ROS …”
Section: Discussionmentioning
confidence: 59%
“…Differential metabolites and metabolic pathways identified in this study might be relevant to human sperm quality. For example, mRNA levels of γ-aminobutyric acid receptors in human sperm are correlated with poor sperm quality [ 43 ]. D-aspartate could protect human sperm via preventing the decrease of motility and the increase of DNA fragmentation and lipid peroxidation [ 44 ].…”
Section: Discussionmentioning
confidence: 99%